Analisis Zakat Produktif Baznas Kota Bogor - Abdul Husenudin; Hari Susanto; Qurroh Ayuniyyah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Poverty is a problem that must be overcome by both government institutions and elements of society, coupled with the current pandemic conditions that have hit almost all countries. This is the background for the author to analyze one of the productive programs, especially at BAZNAS Bogor City. This type of research is descriptive research that uses a qualitative approach. Descriptive research is research that aims to describe systematically, factually, and accurately about facts in a particular population or area. The data sources that the researcher uses are primary data sources from BAZNAS Bogor City and beneficiaries of the Z-CHICK program and secondary data sources from books, journals and previous research. Data collection techniques through observation, in-depth interviews and documentation techniques. The data analysis technique used the SWOT analysis technique. The results of data analysis regarding the position of the Z-CHICK program using a SWOT analysis based on the internal-external matrix (IE-Matrix) with a total IFAS score of 2.08 and a total EFAS score of 3.3. This shows that the condition of the Z-CHICK program is in cell II which can be interpreted as a growing and built phase, which means that the choice of strategy in quadrant II is integration and intensive strategy in which the product of the Z-CHICK program must be developed by conducting innovation and expanding market share such as marketing on social media can be the most appropriate in this section. Keywords: Bogor City National Development Planning Agency, Z-CHICK Program, SWOT Analysis